2003
DOI: 10.1080/0142159031000092779
|View full text |Cite
|
Sign up to set email alerts
|

Development of training of trainers programmes and evaluation of their effectiveness in Istanbul, Turkey

Abstract: This report presents an evaluation of the impact of the 'Training of Trainers' (TOT) courses conducted since 1997. The effects of TOT programmes were studied using a questionnaire given to the course participants immediately after and again following a minimum period of six months after completion of the course. The 85 participants included in this analysis were medical teachers from the Istanbul Faculty of Medicine, of whom 17% were instructors, 39% were associate professors and 44% full professors. Some 72% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…In accordance with this observation, the topic that was found to be effective in implementing a change in most of the faculty members' teaching activities was that for largegroup presentations, an activity that is common for all faculty members. In two other studies conducted in Turkey, the major impact of the course on the teaching practices of faculty members was reported to be on large-group teaching, which was modified by the improvement of didactic lectures (15,16,21). Junior faculty members, however, benefited more from demonstration and coaching, probably because they are more involved with skills training than full professors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In accordance with this observation, the topic that was found to be effective in implementing a change in most of the faculty members' teaching activities was that for largegroup presentations, an activity that is common for all faculty members. In two other studies conducted in Turkey, the major impact of the course on the teaching practices of faculty members was reported to be on large-group teaching, which was modified by the improvement of didactic lectures (15,16,21). Junior faculty members, however, benefited more from demonstration and coaching, probably because they are more involved with skills training than full professors.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies (15,17) of faculty training programs (conducted in Turkey) have evaluated the opinions of participants about the efficiency of the training program. Other studies (16,21) aimed to elucidate the educational impact of the newly acquired knowledge and skills upon individual and occupational performances in the professional life of the participants.…”
mentioning
confidence: 99%
“…The lack of effective learning of skills, lack of time to use them and limited resources are some lacunae that decrease the utility of these workshops (Whitehouse, 1997), and their regular upgradation for the reinforcement of psychomotor skills and a refresher course of one day are some improvements suggested (Purandare & Vagha, 2015). However, other studies have reported a positive impact of these training courses stating that the faculty used the skills learnt and it improved their interaction with students (Yolsal et al, 2003;Godfrey et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Training implementation needs to focus on professional leadership trainers who can also act as role-models, give practical hints, and initiate coaching techniques to solve practical challenges (cf. [ 35 ]).…”
Section: Discussionmentioning
confidence: 99%